Circulating tumor DNA in colorectal cancer: biology, methods and applications - Han Chen; Yang An; Chentong Wang; Jiaolin Zhou (Discover Oncology)
Abstract In the practice of colorectal cancer (CRC), traditional tumor tissue analysis is limited by intratumoral and intertumoral heterogeneity and its invasive nature. Circulating tumor DNA (ctDNA) analysis, a promising liquid biopsy approach, has been increasingly explored in clinical studies. Biologically, ctDNA is characterized by tumor-specific diversity and rapid clearance from circulation, enabling real-time, dynamic, and repeatable assessments. Technologically, PCR- and NGS-based downstream analysis methods have been developed and validated. However, variables in pre-analytical and analytical procedures underscores the need for standardized protocols. Compared with clinicopathology-based risk stratification, ctDNA-based molecular residual disease detection has demonstrated significant potential in guiding treatment decisions. Qualitative and quantitative changes in ctDNA have also shown predictive and prognostic value during neoadjuvant or adjuvant treatment, as well as in later-line treatment for metastatic CRC. Specific molecular aberrations in ctDNA can not only assist in identifying candidates for targeted therapies but also reveal resistance mechanisms. Additionally, emerging research is exploring the potential of ctDNA in early cancer detection. Overall, as a novel biomarker, ctDNA holds substantial promise in advancing clinical practice. This review focuses on the biological characteristics, pre-analytical variables, and downstream analysis methods of ctDNA and summarizes its role across various clinical scenarios in CRC.